The adiposity rebound in the 21st century children: meaning for what? - Min Jae Kang (Korean Pediatric Society, 2018)
With the increase in the prevalence of overweight and obesity worldwide, early adiposity rebound, which is known to have a strong association with obesity, has recently been a focus of research. Early adiposity rebound is conventionally known to have a close relationship with non-communicable diseases. However, novel insights into early adiposity rebound have implied an acceleration of growth and puberty, which is directly reflected in the trends in the timing of adiposity rebound, in the 21st century compared with in the past. Furthermore, the observation that lean mass changes rather than fat mass changes show a more similar pattern to body mass index trajectories is interesting. In this article, the later outcomes and risk factors of early adiposity rebound are briefly summarized, and the current trends in the timing of adiposity rebound and novel insights into its relationship with body composition are reviewed.